KNOWLEDGE, ATTITUDE, AND PRACTICE OF HEALTHCARE PROFESSIONALS REGARDING INFECTION PREVENTION AT THE TERTIARY CARE HOSPITAL OF PESHAWAR KPK - BIBI, S; KHAN, FU; SAJJAD, S (Biological and Clinical Sciences Research Journal, 2024)
Occupational health and safety is a crucial element in every organization, especially in a health care setting. Health care workers (HCWs) play a role as vectors and reservoirs for the spread of infection from patient to patient and staff as well. Infection control and prevention practices are essential elements of quality health care and patient safety in health facilities. Objectives: This study was aimed at assessing the levels of knowledge, attitude, and practice scores of the HCWs towards infection control at three public sector hospitals in Peshawar KPK. The study will help policymakers in the design and development of appropriate infection prevention programs and strategic plans by identifying the gap in infection control practices. Method: An institution-based cross-sectional study was conducted to assess the knowledge, attitudes, and practices of nurses regarding infection prevention and control by using a validated and structured questionnaire in three tertiary care hospitals in KPK. The sample size was calculated by using the Raosoft calculator, and the sample size was 318 nurses from these three hospitals, including those nurses who were willing to participate in the study and nurses who had more than one year of experience. Data was analyzed using SPSS version 22. Result: The participants were 55% male and 45% female; 55% were married, 42% were unmarried, 2% were divorced, 51% were diploma holders, 49% were degree holders, and most of the participants were charge nurses, which is 89%, and 11% were working in different administrative positions. Most of the participants who completed the survey were working in intensive care units, which is 66%, and others working in general wards and OPDs. 61% of nurses got information about safety precautions from training, 61% and 29% from books, and 10% from other resources. Participants who got training were 52%, and 48% of participants did not get any training on infection control precautions. Nurses who had knowledge about safety precautions were 84%; only 16% had not enough knowledge about infection control precautions. In attitude and practice about infection control, 58% were in compliance with practice, and 88% showed a positive attitude regarding infection control practices. Conclusion: In the conclusion, we can say that there is enough knowledge among nurses regarding infection control practice, but implementation of this knowledge in practice should be ensured by doing strict supervision of infection control practices in every health care facility.